Manajemen Strategi Program Tahfidz Al-Quran di Pondok Pesantren Tebuireng 08 Banten - Asmawati Asmawati; Maulana Nur Kholis; Ashari Ashari (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This research is motivated by the importance of achieving the success of the tahfidz program at the Tebuireng 08 Islamic Boarding School in Banten, which faces a number of limitations in strategic management aspects. Therefore, this research focuses on planning, evaluation, and exploration of internal and external factors that have the potential to influence the success of the tahfidz program. The theoretical framework used in this research is the theory of strategic management and the theory of Al-Qur'an memorization, which are considered relevant to understanding the dynamics of the implementation of the tahfidz program in Islamic boarding schools. This research uses a qualitative approach with the aim of digging in depth information related to the strategies, mechanisms, and practices of implementing the tahfidz program at the Tebuireng 08 Islamic Boarding School. The data collection process was carried out through in-depth exploration so that a real picture of the program planning and implementation was obtained. The results of the study indicate that the tahfidz program is implemented through tiered stages starting from the formulation of the institution's vision, mission, and objectives, then translated into the form of a tahfidz program as the main program. The findings of this study confirm that the planning of the tahfidz program at the Tebuireng 08 Islamic Boarding School (Pondok Pesantren Tebuireng 08) adheres to strategic management principles, particularly through a trend-watching mechanism that takes into account the internal and external conditions of the Islamic boarding school. This makes the planning more implementable and focused on achieving the desired goals. Furthermore, the program's success is supported by a continuous evaluation mechanism that allows for dynamic improvements and adjustments. Thus, this study emphasizes that the success of the tahfidz program is determined not only by spiritual aspects, but also by strategic management that is systematic, planned, and adaptive to environmental changes.